2018
DOI: 10.2174/1874205x01812010041
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia in Patients with Spinocerebellar Ataxia 3 - Machado-Joseph disease: An Underestimated Diagnosis?

Abstract: Background:Spinocerebellar Ataxia type 3 (SCA3) or Machado-Joseph Disease (MJD) is characterized by cerebellar, central and peripheral symptoms, including movement disorders. Dystonia can be classified as hereditary and neurodegenerative when present in SCA3.Objective:The objective of this study was to evaluate the dystonia characteristics in patients with MJD.Method:We identified all SCA3 patients with dystonia from the SCA3 HC-UFPR database, between December 2015 and December 2016.Their medical records were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…OMD has been described in various Spinocerebellar ataxias including SCA1,[ 85 ] SCA2,[ 86 ] SCA3,[ 87 ] SCA8,[ 88 ] SCA12[ 89 ] and SCA36. [ 90 ] OMD may occur during the course of the illness, or rarely, can be the presenting feature.…”
Section: G Enetic C Ausesmentioning
confidence: 99%
“…OMD has been described in various Spinocerebellar ataxias including SCA1,[ 85 ] SCA2,[ 86 ] SCA3,[ 87 ] SCA8,[ 88 ] SCA12[ 89 ] and SCA36. [ 90 ] OMD may occur during the course of the illness, or rarely, can be the presenting feature.…”
Section: G Enetic C Ausesmentioning
confidence: 99%
“…Dystonia is one of the most common extrapyramidal manifestations in SCA3. Previous studies have reported a prevalence of dystonia between 3.7 and 33.3% in SCA3 ( 16 , 17 ). Dystonia and ataxia may share some overlapping pathologies, such as synaptic transmission and neurodevelopment ( 18 ).…”
Section: Discussionmentioning
confidence: 93%
“…12,13 Features of childhood-onset SCA3 are similar to the adult onset form, but appear to be more rapidly progressive. 11 A range of movement disorders, including dystonia, has been reported in SCA3 and some of the other inherited ataxias, 21 leading to support for the hypothesis that the cerebellum might play a role in the generation of dystonia. 32 Dystonia has been reported as a feature in childhood-onset SCAs, 11,12 but to our knowledge, tongue dystonia in SCA3 has never been documented.…”
Section: Discussionmentioning
confidence: 99%